STUDI TEKNOLOGI PERENGKAHAN PANAS DAN PENJENUHAN TRIGLISERIDA CRUDE PALM OIL PADA KONDISI BASA DENGAN TWO STAGES ELECTROCHEMICAL THERMAL CRACKING REACTOR - Trisnaliani, Lety; Purnamasari, Indah (Politeknik Negeri Sriwijaya, 2014)
The study was experienced using electrolyze by using two stages electrochemical thermal cracking reactor, zeolyte as catalyst, silver as cathode and cuprum as anode. In this research, we used electrolyte solution for 2 kinds of pH which was pH 10 and pH 12 of Potassium Hydroxide (KOH) and different voltage which was 2,4,6,8,10 and 12 volt. It worked in 1 atmosphere with electrolyze for 1 hour, heating till reaching temperature 80 oC for 1 hour, fogging process for 1 hour, and heating without electrolyze nor fogging about 30 minutes. From lubricity analyze, this product is a fuel with high lubricity. The analyzer showing that cracking of triglyceride of crude palm oil has same characteristics with diesel.